PERAN ORANG TUA DAN GURU DENGAN PENCEGAHAN PERILAKU MEROKOK SISWA SMP N 1 BANGUNTAPAN BANTUL - Dwi Widiyaningsih; Ade Kattalia Hermaini; Rustiana Setyowati (ALBAMA: JURNAL BISNIS ADMINISTRASI DAN MANAJEMEN, 2023)
Background: The results of the preliminary study, namely the researchers saw that there were high school children who smoked in the SMP N 1 Banguntapan Bantul Yogyakarta environment, the researchers also interviewed several students regarding the role of parents and teachers and found that there were parents of students who smoked and teachers who brought cigarettes to school. Based on this preliminary study, the researchers saw that there were high school students who smoked in the SMP N 1 Banguntapan Bantul Yogyakarta 2023 environment. Objective: Knowing association between the role of parents and teachers with the prevention of smoking behavior in class VIII students in junior high school 1 banguntapan bantul yogyakarta 2023. Method: This research is a quantitative study with a cross sectional approach. The sampling technique used is proportionate random sampling. with the number of samples taken were 62 Class VIII students in junior high school 1 Banguntapan Bantul Yogyakarta. The research instrument used was a questionnaire. Data analysis using Chi Square. Result: There is a association between the role of parents and the with the prevention of smoking with a P value (37,455) > P tabel (5.991). There is a association between the role of teacher's ole and the prevention of smoking with a P value (32,193) > P tabel (5.991)